Efficacy and safety of acupuncture-point stimulation combined with opioids for the treatment of moderate to severe cancer pain: a network meta-analysis of randomized controlled trials - Zhang, Qinglin; Yuan, Yuntong; Zhang, Meiling; Qiao, Baohua; Cui, Yiyuan; Wang, Ying; Feng, Li (Frontiers in Oncology, 2023)
Background: Pain presents one of the most common and troublesome symptoms of cancer. Although potential positive effects of Acupuncture-Point Stimulation (APS) on cancer pain have been observed, knowledge regarding the selections of the optimal APS remains unclear because of a lack of evidence from head-to-head randomized controlled trials. Objective: This study aimed to carry out a network meta-analysis to compare the efficacy and safety of different APS combined with opioids in treating moderate to severe cancer pain and rank these methods for practical consideration. Methods: A comprehensive search of eight electronic databases were searched to obtain randomized controlled trials involving different APS combined with opioids for moderate to severe cancer pain. The Cochrane Handbook tool was employed to assess the risk bias of included studies. Network meta-analysis was performed using Stata/SE16.0. Results: A total of 48 studies, eight interventions and 4026 patients with cancer pain were included eventually. Network meta-analysis showed that a combination of APS and opioids was superior in relieving moderate to severe cancer pain and reducing the incidence of adverse reactions such as nausea, vomiting, and constipation compared to opioids solely(p<0.05). Moreover, fire needle was more helpful for moderate to severe cancer pain than other interventions (Odd ratio [OR]= 0.25, 95% CI= 0.18–0.36). The SUCRA rank and bubble plots results also indicated that fire needle combined with opioids achieved the best pain relief effect. Conclusions: APS seemed to be effective in relieving cancer pain, and reducing opioid-related adverse reactions. Fire needle combined with opioids may be a promising intervention to reduce moderate to severe cancer pain as well as reduce opioid-related adverse reactions. However, the evidence was not conclusive. More high-quality trials investigating the stability of evidence levels of different interventions on cancer pain must be conducted.